An Enhanced Ant Colony Algorithm-Based Low-Carbon Distribution Control Method for Logistics Leveraging Internet of Things (IoT) - Liu, You-wu; Li, Jun-long; Liu, Ming-yue; Jiao, Bian-bian (Wireless Communications and Mobile Computing, 2023)
This paper presents a low-carbon vehicle routing optimization model to reduce energy consumption and carbon emissions in logistics and distribution. The model is solved using a hybrid algorithm of simulated annealing and ant colony optimization. It enhances the information pheromone concentration update process and directionality by introducing a carbon emission factor and a multifactor operator. Additionally, an adaptive elite individual reproduction strategy is employed to improve algorithm efficiency. In this case study focusing on cold chain logistics distribution, both the model and algorithm under consideration were evaluated. The findings affirm the effectiveness of the model in reducing carbon emissions and demonstrate the efficiency and robustness of the algorithm. Through this analysis, the paper sheds light on environmentally sustainable practices in logistics distribution.